The mantle of the prophet religion and politics in Iran - Mottahedeh, Roy P. 1940- (Oneworld, 2000)
Drawn from the first-hand accounts of eye-witnesses, Roy Mottahedeh's gripping account of Islam and politics in revolutionary Iran is widely regarded as one of the best records of that turbulent time ever written. Roy Mottahedeh is Gurney professor of Islamic History at Harvard University. An internationallly renowned expert, he has published extensively in this field and his academic awards include a Guggenheim and a MacArthur Prize Fellowship.